Polish Jewish re-remembering : studies-sketches-interpretations - Żurek, Sławomir Jacek (2023)
"The title of this monograph, 'Polish-Jewish Re-Remembering', refers to the post-1989, thirty-year-long process of reviving attention to Polish-Jewish relations in historical, cultural, and literary studies, including the impact of Jews on the development of Polish culture, their presence in Polish social life, and the relationships between Jews and non-Jews in Poland. The book consists of four parts: the first focuses on Polish, Jewish and Polish-Jewish Literature (dealing mainly with pre-1939 literary works); the second, on the post-war literary output of the Polish-Jewish writer Arnold Słucki (1920-1972); the third, on Polish-Israeli literary images in the works of writers who were active in Israel (1948-2018); and the fourth, on recent (after 2000) Polish Holocaust literature